Urgensi Tarjih al-Hadis di Era Kontemporer - Tohri, Zia (SHAHIH (Jurnal Ilmu Kewahyuan), 2023)
The tarjih method emerged due to the occurrence of hadiths that were outwardly contradictory between one proposition and another, when this happens it can be resolved using the al jam'u wa al taufiq method. And if this tarjih method cannot be used then the alternative is al tawaquf (suspended) temporarily, while hadith researchers study the hadiths, whether the hadith will be tarjih or jasakh. However, as time goes by, hadith researchers no longer use the tarjih method because everything that is to be tarjih can be accessed on various platforms such as Maktabah Syamilah, Politik al-Sittah, Politik al-Tis`ah, Jawami` al-Kalim. However, there are still many law enforcers who do not understand the tarjih method, so that when determining the law they make mistakes and make mistakes which can result in very fatal errors in deciding a case or law. If hadith researchers understand how to apply the tarjih method today, where all hadiths can be accessed via the internet, then the tarjih method is not relevant for use today, provided that the hadith researchers understand what is meant by the tarjih method, the conditions - conditions and rules. However, on the other hand, when they do not understand what is meant by the tarjih method and how to use it, this method must be used even though developments in the times are so sophisticated, so that fatal errors do not occur when deciding on a law or deciding on a solid hadith. For further discussion, this article explains what is meant by the tarjih method and its requirements and whether the tarjih method is relevant to use nowadays, considering that everything you want to search for is very easy to access via the internet.